POTENSI ANTIBAKTERI EKSTRAK DAUN KOPASANDA (Chromolaena odorata L) TERHADAP Pseudomonas aeruginosa DAN Staphylococcus aureus - Nurhanifah; St. Ratnah; Rante Pakadang, Sesilia (Jurnal Kefarmasian Akfarindo, 2022)
Infectious disease is a human health problem that will develop from time to time. Skin infections can be caused by bacteria. Kopasanda Leaf Extract contains secondary metabolite compounds that act as antibacterial agents. The purpose of this study was to determine the class of chemical compounds and the antibacterial activity of Kopasanda leaf extract (Chromolaena odorata L) against Pseudomonas aeruginosa and Staphylococcus aureus based on the diameter of the inhibition zone. The working method used is the manufacture of simplicia, extraction, phytochemical screening, antibacterial activity testing with the disc diffusion method. Based on the results of the study, the average inhibition zone on Pseudomonas aeruginosa 2% was 11.3 mm, 4% concentration was 13.3 mm, 8% concentration was 19.3 mm and the positive control was 16.6 mm and the negative control was obtained. 0 mm. While the results of the measurement of the diameter of the inhibition zone on Staphylococcus aureus with a concentration of 2% of 12.6 mm, 4% concentration of 15.6 mm, 8% concentration of 18.6 mm, and 16.3 mm in positive control and 0 mm in negative control. which means it has no inhibition zone. The conclusion of this study was that all concentrations of kopasanda leaf extract used had antibacterial potential against Pseudomonas aeruginosa and Staphylococcus aureus.